KAJIAN MODAL SOSIAL PADA KELOMPOK TANI PADI SAWAH SUKA MAJU DI DESA TAWAANG BARAT KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Karundeng, Raydi; Ngangi, Charles Reijnaldo; Ruauw, Eyverson (Sam Ratulangi University, 2022)
This study aims to examine and describe the social capital (trust, norms, networks, reciprocal relationships) in the up-and-coming rice paddy farmer group in Tawaang Barat Village, Tenga District, South Minahasa Regency. The sampling method used is purposive sampling. The data used in this study is primary data supported by observations and questionnaires and secondary data. The results showed that the Suka Maju Farmer Group had high social capital, namely regarding trust, social norms, social networks, and reciprocal relationships with a social capital index of 78.43%. Group members assume that social capital is indispensable in social life, especially in farming and social capital must be continuously developed so that it becomes one of the cultures in an organization or society so that it can further strengthen the relationship between fellow farmers in farming.